Subject-specific pedagogy: Development of biology teaching materials based on van hiele thinking theory - Akbar Handoko; Santi Sartika; Bambang Sri Anggoro (JPBIO (Jurnal Pendidikan Biologi), 2021)
The learning tools used by teachers at the junior high school level are inadequate. This research aims to develop teaching tools based on Van Hiele thinking theory. This research method was research and development. Data collection was carried out using expert design validation sheets covering material, media, language, student response questionnaires, and teacher assessment sheets. The research results indicate that the percentage of science teacher (biology) assessments on the product were 76.5% and with proper criteria, after revision, the results show a higher percentage was 83% with very feasible criteria. The preliminary results or limited field trials of students have a percentage was 83% with very feasible criteria. Meanwhile, large group product trials have a percentage was 84%. This shows that the results of large group trials are higher when compared to limited trials (84%> 83%). So, concluded of this research that the Subject Specific Pedagogy based on Van Hiele thinking theory is very feasible to use.Keywords: Subject specific pedagogy, van hiele theory, teaching tools